2006
DOI: 10.1002/pssa.200669598
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of ternary thallium chalcogenide compounds

Abstract: The electronic structures of the ternary thallium chalcogenide compounds, TlGaSe 2 and TlGaS 2 are studied, using the linear muffin-tin orbital (LMTO) method. The calculated band dispersion shows that both compounds are indirect gap semiconductors. For both compounds, the top of the valence bands is located at Γ. For TlGaSe 2 , the bottom of the conduction band is located along the Z(0, 0, -5)-L(0.5, 0.5, -0.5) line. For TlGaS 2 , the bottom of the conduction band is located along the Γ -Y(0, 1, 0) line. An in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 9 publications
(7 reference statements)
6
37
0
Order By: Relevance
“…This, in their turn, indicates that TlGaSe 2 is an indirect gap semiconductor with the indirect gap from  to -Y line of 0.87 eV, while the direct gap at the -point is 0.99 eV. Indirect scenario of bands at the energy gap is favoured by other works, e.g., [18][19][20][21] too. However, the particular indirect schemes vary from work to work according to the earlier works [18,19]: the additional valence band maximum on Y line might be responsible for the indirect scenario.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This, in their turn, indicates that TlGaSe 2 is an indirect gap semiconductor with the indirect gap from  to -Y line of 0.87 eV, while the direct gap at the -point is 0.99 eV. Indirect scenario of bands at the energy gap is favoured by other works, e.g., [18][19][20][21] too. However, the particular indirect schemes vary from work to work according to the earlier works [18,19]: the additional valence band maximum on Y line might be responsible for the indirect scenario.…”
Section: Resultsmentioning
confidence: 85%
“…However, the particular indirect schemes vary from work to work according to the earlier works [18,19]: the additional valence band maximum on Y line might be responsible for the indirect scenario. Nevertheless, the later works [20,21] and the present calculations, which used more advanced computation techniques, commonly advocate the conduction band bottom that is not in -point. At the same time, the just mentioned works specify different positions of this bottom in the BZ.…”
Section: Resultsmentioning
confidence: 87%
“…The theoretical studies on the electronic band structure of TlGaSe 2 crystals have been accomplished using the pseudopotential method [34], the screened-exchange local density approximation [35] and the linear muffin-tin orbital method [36]. Abdullaeva and Mamedov [34] and Johnsen et al [35] found that the valence band maximum is located at the G point of the Brillouin zone, while the conduction band minimum occurs along the GeY direction.…”
Section: Resultsmentioning
confidence: 99%
“…1) • [10]. The band structure of the TlGaSe 2 layered crystal has been calculated initially by means of the semi-empirical pseudopotential method [11,12], and next by ab initio methods [13], however in an inappropriate Brillouin zone. Our recent ab initio DFT-based calculations within a relevant BZ of the monoclinic base-centered lattice [14] have revealed that the band structure of TlGaSe 2 exhibits a complicated form in the vicinity of the energy gap, see Fig.…”
Section: Introductionmentioning
confidence: 99%